Pengaruh Motivasi Langsung Dan Tidak Langsung Terhadap Kinerja Pegawai Pada Dinas Kelautan Dan Perikanan Kabupaten Paser - Achmad Syahruddin; Amir Hamzah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The formulation of the problem in writing this thesis is: is there a direct and indirect motivational effect on the performance of employees at the Maritime Affairs and Fisheries Service in Paser Regency. And which variable among the direct and indirect motivational variables has the dominant influence on employee performance. The benefit to be achieved in this research is that it can be used to improve the performance of civil servants in the future. From the results of multiple linear regression analysis, we get the function equation Y = 0.607+0.466X1+0.330X2. From these results it can be seen that the motivational variable has a positive effect on employee performance at the Maritime Affairs and Fisheries Office of Paser Regency. This effect is also explained by the R2 value (coefficient of determination) of 0.325, which means that the variables studied have an effect of 32.5% and the remaining 67.5% is influenced by other variables not included in this study. The regression coefficient (R), which describes the strong relationship between the independent variables and the dependent variable can be seen in the test, which is equal to 0.594. This means that there is a moderate relationship between the independent variables and the dependent variable. Fcount value ˃ Ftable or 12.818 ˃ 3.1951 and probability value 0.000 ˂ 0.05. Shows that direct and indirect motivational variables have a simultaneous (together) effect on employee performance. Of the direct and indirect motivational variables, the direct variable has a dominant influence, this is evidenced by the value of tcount ˃ ttable or 3.3777 ˃ 1.6779 and the smallest probability value of 0.001 ˂ 0.05 Seeing the results of the discussion above, it is concluded that the initial hypothesis proposed is accepted, because the initial hypothesis states that the dominant variable is direct motivation variable (X1).